Extremely Strong and Tough Biodegradable Poly(urethane) Elastomers with Unprecedented Crack Tolerance via Hierarchical Hydrogen-Bonding Interactions - Guo, Rui (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 Wiley-VCH GmbH.